Amphotericin B delays both scrapie agent replication and PrP-res accumulation early in infection. - McKenzie, D (1994)
Amphotericin B delays the onset of clinical symptoms in hamsters infected with scrapie agent strain 263K. Here we show that accumulation of a scrapie-specific isoform of the prion protein (PrP-res) and agent replication were delayed early in amphotericin B-treated animals. By 8 weeks postinfection, only untreated animals exhibited clinical symptoms of scrapie infection whereas PrP-res levels and titers were similar in treated and untreated animals. This suggests that although PrP-res accumulation and agent replication are linked, they are not the sole factors required for the onset of clinical disease.